Friendlyvision : Fred Friendly and the rise and fall of television journalism - Engelman, Ralph (Columbia University Press, 2009)
Fred Friendly (1915-1998) was the single most important personality in news and public affairs programming during the first four decades of American television. Portrayed by George Clooney in the film Good Night and Good Luck, Friendly, together with Edward R. Murrow, invented the television documentary format and subsequently oversaw the birth of public television. Juggling the roles of producer, policy maker, and teacher, Friendly had an unprecedented impact on the development of CBS in its heyday, wielded extensive influence at the Ford Foundation under the presidency of McG.